Influence of the Roofing System on the Seismic Performance of Single-Layer Spherical Reticulated Shell Structures - Wenliang Li; Xudong Zhi; Feng Fan (Buildings, 2022)
The seismic performance of a single-layer spherical reticulated shell is the key problem to be solved in the design and analysis of this structure. In previous studies, the influences of roofing systems on the seismic performance of shells were usually ignored, resulting in large discrepancies between the results of analyses and the actual stress states of shells. In this paper, the finite element analysis method is applied to a shell with a roofing system, and the applicability of the method is proven by static loading experiments. The influences of roofing systems on the seismic performance of shells are obtained from seismic response curves, the proportions and distributions of plastic members and the failure behaviours of the shells during strong earthquakes. The mechanism of the influence of the roofing system on the seismic response of a shell is revealed by analysing the damage of purlin joints and the energy consumption of the components of the shell. The relationships that describe the influence of different parameters of reticulated shells and roofing systems on the seismic response of the shells are studied, and the results show that the roofing system can greatly change the seismic response and failure of a shell under strong earthquake conditions.